When We're Asked to Change: The Role of Suppression and Reappraisal in Partner Change Outcomes. (August 2022) - Sisson, Natalie M.; Wang, Grace A.; Le, Bonnie M.; Stellar, Jennifer E.; Impett, Emily A.
Receiving a request to change from a romantic partner can evoke intense emotional responses that hinder change progress and conflict resolution. As such, investigating how those being asked to change (i.e., change targets) regulate their emotions through key intrapersonal strategies (i.e., suppression and reappraisal) will lend crucial insight into promoting change success. Utilizing laboratory-interaction (Study 1; N = 111 couples) and experience-sampling methods (Study 2; N = 2178 weekly reports from an 8-week diary), we assessed targets' regulation strategies, change progress, and the extent to which they met their partner's ideals. Preregistered analyses demonstrated that targets' use of suppression was not linked to better or worse change outcomes. However, targets' use of reappraisal was linked to better change outcomes as rated by both partners. Additional analyses revealed that targets' suppression was linked to targets meeting their partner's ideals more in the short term but less over time, whereas targets' reappraisal was linked to targets meeting their partner's ideals more in both the short term and over time. These findings highlight reappraisal as a key strategy for promoting successful partner change.